2006
DOI: 10.1248/cpb.54.1722
|View full text |Cite
|
Sign up to set email alerts
|

The Permeation of Nalmefene Hydrochloride across Different Regions of Ovine Nasal Mucosa

Abstract: Nasal drug delivery has been generating widespread interest in the drug delivery field because it could not only be used in local treatment but also in systemic administration. Various properties of nasal drug delivery made it an alternative route for intravenous and oral administration, such as bypassing of enzymatic or acidic degradation and exempting the first-pass hepatic metabolism; the relatively large epithelial surface, porous endothelial membranes and highly vascularized epithelium also maintained the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…Du et al reported that the morphology of the ovine mucosa is more comparable to that of humans because of the presence of ciliated and nonciliated cells, basal cells, goblet cells, and serous glands [39]. To correlate in vitro drug release behaviour of drug from Lzp-PLGA-NPs, ex vivo study on sheep nasal mucosa was performed using Franz diffusion cell.…”
Section: Methodsmentioning
confidence: 99%
“…Du et al reported that the morphology of the ovine mucosa is more comparable to that of humans because of the presence of ciliated and nonciliated cells, basal cells, goblet cells, and serous glands [39]. To correlate in vitro drug release behaviour of drug from Lzp-PLGA-NPs, ex vivo study on sheep nasal mucosa was performed using Franz diffusion cell.…”
Section: Methodsmentioning
confidence: 99%
“…Within one hour of the sacrifice of the animal, the nasal cavity was fully exposed by a longitudinal incision through the lateral wall of the nose while avoiding the damage of the septum. Subsequently, the mucosa was carefully removed and immediately immersed in normal saline (Du et al, 2006 ). Two segments were carefully separated from the anterior and the posterior regions of the mucosa in the nasal cavity.…”
Section: Methodsmentioning
confidence: 99%
“…The nasal cavity was exposed with a longitudinal excision through the lateral wall of the nose without damaging the septum (Vandekerckhove et al, 2009). The mucous membrane was then carefully removed and immediately washed and immersed in ice-cold Ringer's solution (Du et al, 2006).…”
Section: Isolation Of Sheep Nasal Mucosamentioning
confidence: 99%